2017
DOI: 10.48550/arxiv.1703.01003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete translating solitons to the mean curvature flow in $\mathbb{R}^3$ with nonnegative mean curvature

Abstract: We prove that any complete immersed two-sided mean convex translating soliton Σ ⊂ R 3 for the mean curvature flow is convex. As a corollary it follows that an entire mean convex graphical translating soliton in R 3 is the axisymmetric "bowl soliton". We also show that if the mean curvature of Σ tends to zero at infinity, then Σ can be represented as an entire graph and so is the "bowl soliton". Finally we classify the asymptotic behavior of all locally strictly convex graphical translating solitons defined ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Wang proved uniqueness of the bowl soliton among entire convex translating graphs [Wan11]. This was improved recently by Spruck-Xiao [SX17], who showed that every entire mean convex translating graph is in fact convex. 4 Without assuming that the translator is graphical, Martin, Savas-Halilaj and Smoczyk proved a uniqueness result for the bowl soliton under rather strong asymptotic assumptions [MSHS15].…”
Section: Introductionmentioning
confidence: 95%
“…Wang proved uniqueness of the bowl soliton among entire convex translating graphs [Wan11]. This was improved recently by Spruck-Xiao [SX17], who showed that every entire mean convex translating graph is in fact convex. 4 Without assuming that the translator is graphical, Martin, Savas-Halilaj and Smoczyk proved a uniqueness result for the bowl soliton under rather strong asymptotic assumptions [MSHS15].…”
Section: Introductionmentioning
confidence: 95%
“…There exist strictly increasing sequences of positive numbers {m 1 i }, {m 2 i }, {n 1 i } and {n 2 i } so that m 1 i < m 2 i and −n 1 i < −n 2 i , for all i > i 0 ;; b. There exist smooth functions: (23) ϕ…”
Section: Thus By Theorem 23 We Getmentioning
confidence: 99%
“…He characterized the bowl soliton as the only convex translating soliton which is an entire graph. Very recently, J. Spruck and L. Xiao [23] have proved that a translating soliton which is graph over the whole R 2 must be convex. R. Haslhofer [9] showed that any strictly convex, uniformly two-convex translator which is non-collapsing is necessarily rotationally symmetric.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Hoffman, Ilmanen, Martín and White [3] showed that no complete translating soliton is the graph of a function over a halfspace in R 2 . Spruck and Xiao [9] showed that complete translating soliton which is a graph over a domain in R 2 must be convex. Also, for the function u :…”
Section: Introductionmentioning
confidence: 99%